Edukacja wielokulturowa i międzykulturowa – wyzwaniem XXI wieku - Łobacz, Małgorzata; Drop, Katarzyna; Janiszewska, Mariola (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
At present, education seems to play a fundamental role in a European society, being perceived as a model of a community based on knowledge. Nevertheless, multicultural and intercultural education presents itsef as a challenge in a XXI century. Nowadays, when migration of various ethnic groups and nations is so ordinary, nurturing proper attitude about it, seems to be of great importance from the earliest stages of upbringing. It entails a respect of a tradition and culture of one’s own country as well as of other ethnic groups and nations. School as an institution of learning ought to ensure proper measures preventing discrimination. Intercultural education serves as a tool to nurture attitude of understanding and acceptance of a cultural differences. It also broadens perception of one’s own identity and a place in a society. Interactions with other nations can serve to promote an attitude of tolerance and dialogue. Multicultural education on the other hand, aims at creating the disposition of respect toward diversity in a local, national and international community. At the same time it presents cultural, ethnic, racial and linguistic differences. The work will include also the concept of stereotype and prejudice as well as dangers resulting from the absence of a proper multicultural and intercultural education.